Investigating students’ perceptions of online learning - Hamizah, Zahari; Siti Ainun Jariyah, Hassan (UPM, 2021)
The outbreak of Coronavirus (COVID-19) since 2020 affected many people. Because of the global pandemic, many colleges and Universities have been forced to go online and no one knows how long the pandemic will last, and hence the teaching style has been switched to online mode (Gopal, Singh & Aggarwal, 2021). Online teaching and learning could be longer than we expected. In this paper, a survey was conducted to investigate the students' perception of online learning. It is important for us, as educators to understands students' perception of online learning to deliver online teaching effectively. There are many challenges in online learning, faced not only by instructors but also by students.